USING COMMUNICATIVE BASED TEACHING MATERIALS THROUGH INSTAGRAM FOR INCREASING CREATIVITY AND SPEAKING SKILLS - Febriani, Suci Ramadhanti; Widayanti, Rizka; Husna, Ilya; Yasmadi, Yasmadi; Guettaoui Bedra, Kddour (Lentera Pendidikan : Jurnal Ilmu Tarbiyah dan Keguruan, 2024)
Using social media and Instagram among students is necessary in the era of globalization. Instagram can be used as a medium for university students to learn Arabic. This research aimed to determine the effectiveness of using Instagram based on communicative teaching materials in the Basic Level Training program in Arabic language courses at the Language Center of UIN Imam Bonjol Padang. This study used a mixed method that described students’ perceptions. The participants were 30 students in the Arabic Language Basic Level Training program. This study showed that the teaching materials used were based on a communicative approach and contextual themes by context-based situations of everyday life. The findings indicated there was a significant effect of using teaching materials on students’ creativity and speaking skills. Moreover, using communicative-based teaching materials accelerated students’ mastery of language creativity and improved speaking skills. This study recommends further research to use a wider sample. Abstrak: Penggunaan media sosial dan Instagram di kalangan pelajar merupakan hal yang diperlukan di era globalisasi. Instagram dapat digunakan sebagai media untuk pembelajaran bahasa Arab di universitas. Penelitian ini bertujuan untuk mengetahui efektivitas penggunaan Instagram berbasis bahan ajar komunikatif dalam mengikuti program Pelatihan Tingkat Dasar pada mata kuliah bahasa Arab di Pusat Bahasa UIN Imam Bonjol Padang. Penelitian ini menggunakan mixed method yang menggambarkan persepsi siswa. Partisipannya adalah mahasiswa program Pelatihan Tingkat Dasar Bahasa Arab yang berjumlah 30 orang. Penelitian ini menunjukkan bahwa bahan ajar yang digunakan didasarkan pada pendekatan komunikatif dan tema kontekstual berdasarkan konteks situasi kehidupan sehari-hari. Temuan penelitian menunjukkan terdapat pengaruh yang signifikan pada penggunaan bahan ajar terhadap keterampilan kreatifitas dan berbicara siswa. Selain itu, penggunaan bahan ajar berbasis komunikatif dapat mempercepat penguasaan kreatifitas berbahasa siswa dan meningkatkan keterampilan berbicara. Penelitian ini merekomendasikan penelitian selanjutnya untuk menggunakan sampel yang lebih luas.